2014
DOI: 10.1007/s10096-014-2158-z
|View full text |Cite
|
Sign up to set email alerts
|

A tailored implementation strategy to reduce the duration of intravenous antibiotic treatment in community-acquired pneumonia: a controlled before-and-after study

Abstract: We previously showed that 40 % of clinically stable patients hospitalised for community-acquired pneumonia (CAP) are not switched to oral therapy in a timely fashion because of physicians' barriers. We aimed to decrease this proportion by implementing a novel protocol. In a multi-centre controlled before-and-after study, we evaluated the effect of an implementation strategy tailored to previously identified barriers to an early switch. In three Dutch hospitals, a protocol dictating a timely switch strategy was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…Early IVPOS of antibiotics is a central pillar of antibiotic stewardship as it reduces costs and intravenous cannula infections and encourages reduced length of hospital stay (149). Several studies have shown that it is safe to switch patients with CAP from intravenous to oral therapy when they become clinically stable (150,151). Definitions of clinical stability vary and a typical definition is given in Box 3 (151).…”
Section: Ivpos and Duration Of Antibioticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Early IVPOS of antibiotics is a central pillar of antibiotic stewardship as it reduces costs and intravenous cannula infections and encourages reduced length of hospital stay (149). Several studies have shown that it is safe to switch patients with CAP from intravenous to oral therapy when they become clinically stable (150,151). Definitions of clinical stability vary and a typical definition is given in Box 3 (151).…”
Section: Ivpos and Duration Of Antibioticsmentioning
confidence: 99%
“…Several studies have shown that it is safe to switch patients with CAP from intravenous to oral therapy when they become clinically stable (150,151). Definitions of clinical stability vary and a typical definition is given in Box 3 (151).…”
Section: Ivpos and Duration Of Antibioticsmentioning
confidence: 99%
“…A controlled intervention study conducted in the Netherlands has shown decreased intravenous treatment durations after the application of a stewardship programme consisting of educational sessions and pocket cards reflecting state-of-the-art treatment for CAP. 5 Comparable results applying similar interventions have subsequently been reported in studies from Norway, the USA and Australia. [6][7][8][9][10] Altogether, the different stewardship programmes resulted in reduced antibiotic exposure for patients with CAP as well as a higher probability for correct empiric antibiotic treatment.…”
Section: Introductionmentioning
confidence: 57%
“…These findings are in line with other studies evaluating stewardship programmes in CAP. [5][6][7][8][9][10] Although the point estimates regarding the odds of receiving ≤3 days of intravenous antibiotic treatment in the follow-up period were beneficial as well, the effect sizes were too large to draw any conclusions. However, the duration was, with a median of under 3 days, already low at baseline.…”
Section: Discussion Key Findingsmentioning
confidence: 94%
“…However, other studies and reviews have supported shorter duration of antibiotic therapy in patients with CAP and suggested that the use of biomarkers, such as PCT, may be useful in guiding both the initiation and the duration of antibiotic treatment 48 , 49 . One group of investigators documented that an implementation strategy, tailored to identify previous barriers to early switch, was associated with a reduced duration of intravenous therapy 50 . Another implemented a dedicated CAP team to manage low-risk, hospitalized CAP patients, which resulted in a reduced hospital length of stay, time to switch from intravenous antibiotics, and antibiotic duration without any adverse events 51 .…”
Section: Antibiotic Treatment Of Community-acquired Pneumoniamentioning
confidence: 99%